2016
DOI: 10.1523/jneurosci.3018-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Less Is More: Semantic Information Survives Interocular Suppression When Attention Is Diverted

Abstract: The extent of unconscious semantic processing has been debated. It is well established that semantic information is registered in the absence of awareness induced by inattention. However, it has been debated whether semantic information of invisible stimuli is processed during interocular suppression, a procedure that renders one eye's view invisible by presenting a dissimilar stimulus to the other eye. Inspired by recent evidence demonstrating that reduced attention attenuates interocular suppression, we test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 57 publications
0
28
3
Order By: Relevance
“…As our study showed that attention load of the task modulated the semantic interference from an unconscious prime, it is important to point out that previous studies have shown that attention also interacts with how stimulus invisibility is achieved under a visual suppression/masking paradigm 33,34 . For example, it has been shown that semantic information is registered when the invisibility is induced by the lack of attention under interocular suppression 34 . How exactly did the task-induced attention load, and any other factors related to task, interacted with interocular suppression in our study will require future studies.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…As our study showed that attention load of the task modulated the semantic interference from an unconscious prime, it is important to point out that previous studies have shown that attention also interacts with how stimulus invisibility is achieved under a visual suppression/masking paradigm 33,34 . For example, it has been shown that semantic information is registered when the invisibility is induced by the lack of attention under interocular suppression 34 . How exactly did the task-induced attention load, and any other factors related to task, interacted with interocular suppression in our study will require future studies.…”
Section: Resultsmentioning
confidence: 63%
“…Participants. Throughout all experiments, all participants (age range: [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] reported normal or corrected-to-normal vision. They reported no history of language deficits and were proficient in English.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, because both selection criteria were applied in a non-crossvalidated fashion as is currently common in the field 3 , 40 42 , the definition of so-called chance performers can at least in part be susceptible to noise (inter-trial variability). As has been explained in detail in Shanks 43 , the flash localization accuracy may be lower in chance than non-chance performers in this experimental session because of performance noise and hence if measured again may increase, a statistical phenomenon referred to as ‘regression towards the mean’.…”
Section: Methodsmentioning
confidence: 99%
“…As a third example, HOTs are based on the idea that sensory representations themselves (first-order processes) are not sufficient for consciousness because such representations Busch et al [92] Eo et al [94] Fahrenfort et al [81] Frässle et al [91] Herman et al [82] Koivisto & Revonsuo [89] Pitts et al [77] previous studies zero full minimal stimulus strength attention 1 Pitts et al [80] Sergent et al [90] Wilke et al [93] 2 3 4 5 6 Figure 2. Examples of previous studies that have explored the space depicted in figure 1.…”
Section: Other Leading Theories Of Consciousnessmentioning
confidence: 99%